Transcriptome, proteome and draft genome of Euglena gracilis - Ebenezer, T; Zoltner, M; Burrell, A; Nenarokova, A; Novák Vanclová, A; Prasad, B; Soukal, P; Santana-Molina, C; O'Neill, E; Nankissoor, N; Vadakedath, N; Daiker, V; et al. (BioMed Central, 2019)
Background Photosynthetic euglenids are major contributors to fresh water ecosystems. Euglena gracilis in particular has noted metabolic flexibility, reflected by an ability to thrive in a range of harsh environments. E. gracilis has been a popular model organism and of considerable biotechnological interest, but the absence of a gene catalogue has hampered both basic research and translational efforts. Results We report a detailed transcriptome and partial genome for E. gracilis Z1. The nuclear genome is estimated to be around 500 Mb in size, and the transcriptome encodes over 36,000 proteins and the genome possesses less than 1% coding sequence. Annotation of coding sequences indicates a highly sophisticated endomembrane system, RNA processing mechanisms and nuclear genome contributions from several photosynthetic lineages. Multiple gene families, including likely signal transduction components, have been massively expanded. Alterations in protein abundance are controlled post-transcriptionally between light and dark conditions, surprisingly similar to trypanosomatids. Conclusions Our data provide evidence that a range of photosynthetic eukaryotes contributed to the Euglena nuclear genome, evidence in support of the ‘shopping bag’ hypothesis for plastid acquisition. We also suggest that euglenids possess unique regulatory mechanisms for achieving extreme adaptability, through mechanisms of paralog expansion and gene acquisition.